Mistakes and complications in orthopaedic-traumatological practice - Korzh, Mykola; Yaremenko, Dmytro; Goridova, Lidia; Romanenko, Konstantin (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
On the basis of a study of literature data and their own researches, aimed at revealing the states, which produced negative effects on bony union processes, the authors analysed mistakes and complications, which caused dysfunctions in the locomotor system and restricted vital activity of patients with different injuries of their bones and joints, as well as after surgical interventions on patients with orthopaedic pathologies. A conclusion is made about a necessity to increase the material and technical basis of medical-prophylactic institutions, reform medical education and training of personnel with introduction of European educational and professional standards.